Chylopericardium Detected by Forensic Autopsy - Gök, Ertuğrul; Fedakar, Recep; Akan, Okan (The Bulletin of Legal Medicine, 2018)
The purpose of this case report is to discuss a case of a 72-year- old woman with chylopericardium determined at forensic autopsy, together with the medicolegal dimensions and a brief review of the literature. She presented to a hospital with gastrointestinal symptoms five days after an assault resulting in injury that could have been resolved with a simple medical intervention. Following surgical treatment of incisional hernia and perforated colonic diverticulitis, the patient’s hemodynamics were stable, and monitoring and treatment were maintained. However, the patient died on the second day of hospitalization. Autopsy revealed that the pericardium was tense and that the cavity was filled with white, chylous fluid. A surgically sutured wound, areas of ecchymosis, membrane and point hemorrhage and adhesive areas were observed in the abdomen. No significant macroscopic findings of peritonitis were observed. Histopathological examination revealed edema in the lungs, expansion of the myocyte cytoplasm in the heart....
Keywords: blunt trauma; autopsy; chylopericardium; causal link